Relational Experiences in School-Based Mentoring: The Mediating Role of Rejection Sensitivity. Issue 8 (November 2018) - Kanchewa, Stella S.; Yoviene, Laura A.; Schwartz, Sarah E. O.; Herrera, Carla; Rhodes, Jean E.
In this study, we examined associations between mentoring relationship quality, rejection sensitivity, and youth outcomes. Participants ( N = 446) were part of a national, random assignment evaluation of Big Brothers Big Sisters of America school-based mentoring programs. Youth in more trusting mentoring relationships demonstrated reductions in teacher-reported behavioral evidence of rejection sensitivity. These reductions, in turn, were positively associated with youth's assertiveness with peers and prosocial behavior. Percentile bootstrap confidence intervals testing indirect effects demonstrated that rejection sensitivity mediated the association between mentoring relationship trust and teacher-reported assertiveness and prosocial behavior. Implications of the findings for theory and practice are discussed.